(untitled) (Annual of the Faculty of Philosophy in Skopje, 2019)
Eating disorders have been known since ancient times, but nowadays they have undergone many changes. The first records of eating disorders have been observed since ancient times, with the Roman emperors, etc. There are written documents on the starvation and end of the menstrual cycle in nuns, since the ninth century. Seneca, for the then lifestyle, said: "People eat to repent and vomit in order to be able to eat again." It essentially represents the difference in the way and style of life and today’s diet, where the main goal is to reduce of body weight. Eating disorders indicate unhealthy eating habits, the attitude to food, and the maintenance of body weight, and a common feature of all dietary disorders is the perception of the body’s perception. Diseases of eating disorders are a significant psychological, sociological and general health problem. The latest world research and their results show that it is necessary to invest on the prevention of these diseases, on the adequate training and education of parents in the formation of healthy eating habits among children, education of the medical personnel in early recognition and risk detection, and later and diseases of eating disorders, education by schools and other professionals who have contact with the population at risk of developing a disorder in the diet. Adolescents represent the most at risk of developing a dietary disorder of any kind, as confirmed in the research. The influence of the modern way of life, the influence of the media, peers, and the whole socio-cultural pressure on the person, and many other external factors, encourage and increase the number of people with eating disorders.